Teater Åttonde Dagen - Helander, Joanna; Persson, Bo (Sweden : Kino Koszyk, 1992)
A film follows the Polish theatre company “Eighth Day Theater” in the period before, during and after the upheavals in Eastern Europe. In the 1980´s the company performed underground in selected monasteries and churches. Soon a few members succeeded in leaving Poland and started touring Western Europe joined by the rest of the company a few years later. As the censorship in Poland eased up, the “Eighth Day Theatre” returned to Poland to witness a rapid transition.
Donated by the Arts and Culture Program, CEU
Duration: 01:18:00
Keywords: Documentary films